Preclinical in vitro and in vivo evaluation of [11C]ORM-13070 as PET ligand for alpha-2C adrenergic receptor occupancy using PET imaging in non-human primates - Piel, Isabel; Constantinescu, Cristian C; de la Puente Bethencourt, David; Bonsall, David R; Rabiner, Eugenii A; Zasadny, Kenneth R; Llopis Amenta, Amy; Wells, Lisa A; Poethko, Thorsten; Prange, Wolfgang; Delbeck, Martina (Journal of cerebral blood flow and metabolism, 2025)
This paper describes the preclinical validation of the radioligand [11C]ORM-13070 and its tritiated analog for addressing selectivity and occupancy of the selective alpha-2C adrenergic receptor (α2CR) antagonist BAY 292 in the cynomolgus brain. BAY 292 is a novel drug candidate being developed for the treatment of obstructive sleep apnea (OSA) via binding to central α2CR. In vitro autoradiography studies with sections from non-diseased post-mortem human caudate revealed an excellent specific binding window (>80%) using [3H]ORM-13070. BAY 292 bound to the same binding site as [3H]ORM-13070 and generated a good specific binding signal, with greater selectivity for α2CR. In non-human primates in vivo, [11C]ORM-13070 demonstrated a reversible behavior, with uptake at baseline highest in striatum (putamen, caudate, ventral striatum, and pallidum) and low in the cerebellar cortex, consistent with the known distribution of the α2CR. A dose dependent increase in receptor occupancy after BAY 292 administration was observed, confirming BBB penetration and target engagement. The estimated EC50 for BAY 292 is 33.39 ± 11.91 ng/mL. This study aimed to demonstrate the suitability of [11C]ORM-13070 as a PET-radioligand for the study of α2CR in the non-human primate brain, and to pave the way for future clinical PET tracer studies with BAY 292.